A Neurocinematic Study of the Suspense Effects in Hitchcock's Psycho - Wang, Yashu; Wang, Yiwen (Frontiers in Communication, 2020)
As a new and rapidly emerging cross-disciplinary research field, neurocinematics focuses on movie research from an empirical perspective, adopting functional magnetic resonance imaging (fMRI) and other cognitive neuroscience technologies as well as theoretical methods. By verifying and exploring relevant film concepts, neurocinematics tries to establish a scientific basis for the movie theory and better understand frontier subjects in movie studies. We designed this experiment to detect audiences' brain activity when watching movies and verify the manipulation power of narrative film. We selected the shower murder scene in Hitchcock's Psycho as the experimental material. The results of the experiment showed that the trends of the audiences' brain activity were almost consistent with the specific movie plots. By observing audiences' brain activity while watching the movie, the experiment verified the specific effect of Hitchcock's set-up of suspense and explored the neurocognitive brain mechanisms behind the suspense effect.